POSISI INDONESIA DALAM MIGRASI INTERNASIONAL DAN PASAR KERJA GLOBAL - Marcelinus Molo; Sugihardjo Sugihardjo (Populasi, 1996)
The contribution of Indonesian work force in the International Labor Market is still very minimal, both in terms of quantity and quality. For this reason therefore, the reorientation of the labor force which is sent abroad from mere household workers to being better skilled workers is a very strategic step in improving on the national foreign exchange position and reducing unemployment. This paper is focussed on the importance of improving on the position of Indonesia in International migration through an anticipative focus on the availability of employment opportunities abroad, in order that the nature and the quality of the work force provided is in accordance with the demand in global labor market.